In the archives with Barbara Harlow. (January 2019) - Carter, Mia
The author discusses in a personal vein her co-operative work with Barbara Harlow since their joint realisation, as teachers of literature, of the lack of knowledge students had of the brutalities of colonialism and occupation against which to read texts. She explains the origins, pedagogical motives and political vision behind the three volumes of historical documents that she co-edited with Barbara Harlow: Imperialism and Orientalism: a documentary sourcebook (Basil Blackwell, 1999); Archives of Empire, Volume I: from the East India Company to the Suez Canal (Duke University Press, 2003); Archives of Empire, Volume II: the scramble for Africa (Duke University Press, 2004).